Procurement and governance management: Development of a conceptual procurement model based on different types of control - Per Erik Eriksson (Management Revue, 2006)
Due to the importance of external suppliers for most companies, procurement and governance management is of utmost relevance for achieving competitive advantage. Research in the field of industrial buying behaviour (IBB) has largely been influenced by transaction cost economics (TCE). However, some TCE research has been rather simplistic; not distinguishing between governance structures and mechanisms, while research in IBB has a surplus of descriptive empirical studies and a critical shortage of analytical and conceptual constructs. This paper aims to address these shortcomings by integrating IBB and TCE in a conceptual model regarding procurement and governance of transactions. The model regards the analytical choice of a suitable combination of governance mechanisms (price, trust and authority) for different types of transactions. Additionally, a procedure for facilitating the achievement of a suitable mechanism mix is developed. The procedure shows how decisions during the buying process, regarding different types of control, will affect the mechanisms' levels in the transaction relationship. The model together with its procedure can serve as a basis for analysing planned purchases, in order to tailor governance mechanisms to transaction characteristics.
Keywords: 650; procurement; governance; control; transaction cost economics; Transaktionskosten; Theorie; Governance-Ansatz